Wind Turbine Blade Nondestructive Testing with a Transportable Radiography System - J. G. Fantidis; C. Potolias; D. V. Bandekas (Science and Technology of Nuclear Installations)
Wind turbines are becoming widely used as they are an environmentally friendly way for energy production without emissions; however, they are exposed to a corrosive environment. In addition, as wind turbines typically are the tallest structures in the surrounding area of a wind farm, it is expected that they will attract direct lightning strikes several times during their operating life. The purpose of this paper is to show that the radiography with a transportable unit is a solution to find defects in the wind turbine blade and reduce the cost of inspection. A transportable neutron radiography system, incorporating an Sb–Be source, has been simulated using the MCNPX code. The simulated system has a wide range of radiography parameters.